Pengaruh Strategi Produk Placement dalam Acara D' Academy Season 6 Terhadap Keputusan Pembelian Produk Luwak White Coffee di Kota Bima - Arrahman; Irma Merdian; Sri Ernawati (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to determine the effect of product placement strategy in the television show D’Academy Season 6 on the purchasing decisions of Luwak White Coffee in Bima City. The research employed an associative method with a quantitative approach. Data were collected through observation, questionnaires using a Likert scale, and literature review. The sample was determined using purposive sampling, consisting of 96 respondents aged over 17 years who had watched D’Academy Season 6. Data analysis was carried out using validity and reliability tests, simple linear regression, coefficient of determination, and t-test with the assistance of SPSS V.26.The results show that the product placement strategy has a positive and significant influence on purchasing decisions for Luwak White Coffee. This is evidenced by the t-value (9.330) being greater than the t-table (1.985) with a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.481 indicates that 48.1% of purchasing decisions are influenced by product placement strategy, while the remaining 51.9% are influenced by other factors outside this study.The conclusion of this study is that the product placement strategy in D’Academy Season 6 plays an important role in increasing purchasing decisions for Luwak White Coffee in Bima City. The researcher suggests that the company continue to improve product quality and strengthen its marketing communication strategy, particularly in product placement, to further increase consumer interest and purchasing decisions